EFFECT OF GRAIN SIZE AND ACTIVATION TIME OF ZEOLITE TO ADSORPTION AND DESORPTION OF NH4OH AND KCL AS MODEL OF FERTILIZER-ZEOLITE MIX - Muhammad Prasanto Bimantio (Universitas Lambung Mangkurat, 2017)
Abstract - Zeolites can be used as adsorbent, ion exchange, catalyst, or catalyst carrier. Application of fertilizer use in the zeolite also be one of the interesting topic. Zeolites in a mixture of fertilizer can use to control the release of nutrients. The purpose of this research is to study the effect of grain size and time of the activation of zeolite to adsorption and desorption of NH4OH and KCl as modeling of ZA and KCl fertilizer, to obtain the value of adsorption rate constant (ka) and desorption rate constant (kd). This research procedure include: the process of adsorption by adding zeolite with various size and time of activation into a sealed beaker glass and let the adsorption process occurs for 24 hours. After 24 hours, the solution was filtered, the zeolite then put in 100 ml of aquadest into a sealed beaker glass and let the desorption process happened for another 24 hours. Three samples with the largest difference solution concentrations looked for the value of the ka and kd. Zeolite configuration with the largest ka is trialed with fertilizer and compared with the value of ka obtained from modeling. The result for NH4OH adsorbate, -50+60 mesh 2 hours configuration zeolite give the largest ka. For KCl adsorbate, -30+40 mesh 4 hours configuration zeolite give the largest ka. The value between modeling and trials with fertilizers are not much different. Keywords: zeolite, ZA fertilizer, KCl fertilizer, mathematical modelling.